Test and detection device and method for full-thickness long-life steel slag asphalt concrete pavement
By performing pretreatment methods such as high-temperature calcination, chemical stabilization treatment and mechanical crushing on steel slag, and optimizing the mix ratio design of asphalt mixture, the durability problem of steel slag in asphalt concrete due to volume expansion is solved, and the long life and high performance of steel slag asphalt concrete is achieved.
Patent Information
- Application Number
- CN202411886831.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, when steel slag is used in asphalt concrete, due to volume expansion problems, the asphalt mixture has durability problems such as cracking and peeling during long-term use.
Through pretreatment methods such as high-temperature calcination, chemical stabilization treatment and mechanical crushing, the content of free calcium oxide in steel slag is reduced and the possibility of hydration reaction after contact with water is reduced. At the same time, the mix ratio design of the asphalt mixture is optimized, the amount of asphalt, the aggregate grading and the addition of modifiers are adjusted, and the water damage resistance and durability of the mixture is improved.
The technical obstacles of steel slag volume expansion have been successfully overcome, the long-term performance stability of steel slag in asphalt mixture has been achieved, the road maintenance cost has been reduced, and the resource utilization of steel industry waste has been promoted.
Smart Images

Figure CN119757424A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel slag asphalt concrete, and in particular to a test detection device and method for a full-thickness long-life steel slag asphalt concrete pavement. Background Art
[0002] Asphalt concrete pavement, as the preferred material for modern highway construction, occupies a pivotal position in my country's highway network with its low noise, high comfort, excellent flatness and convenient maintenance characteristics. With the total mileage of national highways exceeding 5.28 million kilometers, a national highway network with expressways as the skeleton, ordinary trunk roads as the blood vessels, and rural roads as the cornerstone has taken shape. In this huge transportation system, asphalt concrete pavement covers more than 90% of medium and high-grade highways, becoming a key infrastructure connecting cities and villages and promoting economic development.
[0003] However, with the rapid development of highway construction and the growing demand for maintenance, the demand for natural aggregates has also increased dramatically. Natural aggregates, such as sand and gravel, are one of the main components of asphalt concrete, and their mining directly affects the cost and sustainability of highway construction. In recent years, the state has introduced a series of policies and regulations aimed at protecting the ecological environment and restricting disorderly mining, such as the "Mineral Resources Law of the People's Republic of China", "Regulations on Sand Mining in the Yangtze River", and "Guiding Opinions on the Management of Sand Mining in Rivers". Although the implementation of these policies has effectively protected the natural environment and reduced the ecological damage caused by over-mining, it has also pushed up the market price of natural aggregates, bringing considerable cost pressure to highway construction.
[0004] In this context, finding alternatives to natural aggregates and realizing resource recycling have become urgent issues to be solved in the field of highway engineering. Steel slag, as an inevitable by-product in the steel production process, its resource utilization has become the key to solving this problem. According to statistics, my country's annual output of steel slag in 2020 reached 160 million tons, but the utilization rate was less than 30%. A large amount of steel slag was simply piled up, which not only occupied precious land resources, but also may pollute the surrounding environment due to long-term weathering and infiltration.
[0005] In the exploration of reducing costs and increasing efficiency of full-thickness asphalt pavement, the innovative application of steel slag asphalt concrete as a wearing layer is gradually becoming a research hotspot in the industry. Due to the thicker structural layer, full-thickness pavement often consumes more material resources, resulting in higher construction costs. In this context, using steel slag, an industrial waste, as aggregate can not only effectively reduce the economic burden of pavement construction, but also actively respond to the call for resource recycling, which coincides with the development concept of green transportation.
[0006] As a byproduct of steel production, steel slag has unique physical and chemical properties, high hardness and wear resistance, and is an ideal choice for preparing high-performance pavement materials. However, the volume expansion of steel slag, especially the significant volume growth of free calcium oxide when it comes into contact with water, has always been the main technical obstacle restricting its widespread application in road materials. Free calcium oxide will undergo hydration reaction when it comes into contact with water to generate calcium hydroxide, accompanied by volume expansion, which may cause durability problems such as cracking and peeling of asphalt mixtures during long-term use. To this end, we proposed a test and detection device and method for full-thickness long-life steel slag asphalt concrete pavement to solve the above problems. Summary of the invention
[0007] The purpose of the present invention is to solve the shortcomings in the prior art and to propose a test and detection device and method for a full-thickness long-life steel slag asphalt concrete pavement.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions: A test and detection device for full-thickness long-life steel slag asphalt concrete pavement includes a base plate, the upper end of the base plate supports a mixing box, both sides of the mixing box are provided with lifting mechanisms, two fixed rails are fixed on the lifting mechanism, two bearing blocks are slidably connected to the two fixed rails, a reciprocating adjustment mechanism is provided at the upper ends of the two fixed rails, the reciprocating adjustment mechanism is connected to the two bearing blocks, a stirring device is installed on one side of the bearing blocks, and the lower end of the stirring device extends into the mixing box, a dust cover cloth is slidably connected to one side of the upper end of the base plate, and the dust cover cloth corresponds to the mixing box.
[0009] Preferably, the lifting mechanism includes fixed blocks fixed on both sides of the mixing box, hydraulic cylinders are fixed through the fixed blocks, support plates are fixed to the ends of the piston rods of the two hydraulic cylinders, the lower ends of the two fixed rails are respectively fixed to one side of the upper ends of the two support plates, and the two hydraulic cylinders are connected using a synchronous control system.
[0010] Preferably, the reciprocating adjustment mechanism includes connecting plates fixed on both sides of the fixed rail, wherein a mounting plate is fixed to the upper end of one of the connecting plates, and a protective box is installed on the upper end of the other connecting plate, a servo motor is installed in the protective box, and the end of the output shaft of the servo motor is connected to a forward and reverse screw, one end of the forward and reverse screw is rotatably connected to one side of the mounting plate, two moving blocks are threadedly sleeved on the forward and reverse screw, and the upper end of the moving block is rotatably connected to two connecting rods, and one end of the two connecting rods on the same side is rotatably connected together to one end of a bearing block.
[0011] Preferably, the stirring device includes a fixed plate fixed to one side of the supporting block, a driving motor is installed on the upper end of the fixed plate, a stirring rod is connected to the end of the output shaft of the driving motor, a plurality of stirring blades are connected at equal intervals around the stirring rod, and a plurality of protrusions are provided at equal intervals on one side of the stirring blade.
[0012] Preferably, second slide grooves are provided on both sides of the upper end of the base plate, second slide blocks are installed in the second slide grooves, a first vertical rod is fixed to the upper end of the second slide block, two second vertical rods are fixed to one side of the upper end of the base plate, and the upper ends of the two first vertical rods and the two second vertical rods are jointly fixed to the four corners of the lower end of the dust cover cloth.
[0013] Preferably, a first slide groove is provided on the guide rail, first sliders are fixed on both sides of the lower end of the bearing block, and a first slider on one side of the lower end of the two bearing blocks is clamped in a first slide groove on the same side.
[0014] Preferably, support columns are fixed at the four corners of the lower end of the mixing box, the lower ends of the support columns are fixed to the upper end of the bottom plate, and a discharge pipe is connected to the middle of the lower end of the mixing box. The discharge pipe is a hose and a valve is installed on the discharge pipe.
[0015] The method of testing and detecting a full-thickness long-life steel slag asphalt concrete pavement comprises the following steps: S1, pretreatment stage, high temperature calcination, chemical stabilization and mechanical crushing are used to treat the steel slag; S2, technical adjustment stage, optimize the mix design of asphalt mixture, adjust the asphalt dosage, aggregate gradation and add appropriate amount of modifier to improve the water damage resistance and durability of the mixture; S3. Finely control the mixing, spreading and pressing processes of the mixture to improve its impermeability and durability; S4, after pretreatment and technical adjustment, steel slag asphalt concrete is prepared; S5. Use X-ray fluorescence analyzer to analyze the composition of three common road aggregates: steel slag, basalt and limestone; S6. By using X-ray diffraction analysis technology to conduct in-depth crystal phase analysis on steel slag aggregates, information about the internal crystal structure of steel slag aggregates was obtained; S7, using electron probe technology to conduct detailed surface analysis of steel slag aggregate to reveal its internal component distribution; S8. Through the analysis of the basic physical and chemical properties of steps S1-S7, a quantitative characterization method for the particle shape and surface characteristics of steel slag aggregate is explored, and key indicators such as shape factor, surface roughness, and porosity are introduced to accurately describe the geometric morphology and surface characteristics of steel slag aggregate; S9. The slag-asphalt interface delamination test method is used to fully characterize the selective absorption and adsorption behavior of slag on asphalt; S10. Conduct mechanical pull-out tests to evaluate the adhesion performance between steel slag aggregate and asphalt; S11. Construct the mechanical characteristic model of slag-asphalt interface; S12, through the slag-asphalt interface delamination test, mechanical pull-out test and interface mechanical characteristic model construction of steps S9-S11, the interaction mechanism between slag aggregate and asphalt and its influence on the performance of asphalt concrete are studied; S13. Use AIMS system to analyze the special particle shape and surface characteristics of steel slag, deeply analyze the influence of steel slag aggregate on the performance of asphalt concrete of different grading types, and explore the influence of the particle shape and surface characteristics of steel slag aggregate on the road performance of asphalt concrete such as water damage resistance, high temperature rutting resistance, low temperature cracking resistance, fatigue resistance, etc. S14. Explore the application potential of aged steel slag in asphalt concrete, design aged steel slag asphalt concrete using the Superpave method, and conduct a comprehensive evaluation of its performance Preferably, according to step S1, high temperature calcination can promote the conversion of free calcium oxide into a more stable compound, thereby reducing its activity; Chemical stabilization treatment adds specific chemical reagents to react with free calcium oxide to form stable compounds, further reducing the risk of volume expansion; Mechanical crushing helps to refine steel slag particles and improve their dispersion uniformity in asphalt mixture, thereby improving the overall performance of the mixture.
[0016] Preferably, according to step S14, the asphalt film peeling test and the tensile failure test method are used, combined with the use of modern scanning electron microscope characterization technology, to clarify the damage mechanism of hot water damage and freeze-thaw damage to the aged steel slag asphalt system; The improvement effect of organic sealants and inorganic anti-stripping agents on the water damage resistance of aged steel slag asphalt concrete was studied.
[0017] The steel slag asphalt concrete in the present invention is an innovative way to reduce costs and increase efficiency of full-thickness asphalt pavements, and has broad application prospects. Through pretreatment and technical adjustments, it successfully overcomes the technical barrier of steel slag volume expansion, laying a solid foundation for the widespread application of steel slag in road materials.
[0018] The material in the present invention not only has excellent wear resistance and anti-skid properties, but also can maintain good volume stability during long-term use, effectively reducing road maintenance costs. In addition, the application of steel slag asphalt concrete also promotes the resource utilization of steel industry waste, and provides strong support for building a green, low-carbon, circular transportation system. At the same time, the steel slag material can be quickly and evenly integrated during detection, thereby improving the accuracy and adequacy of detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a structural diagram of the present invention; Figure 2 It is a connection structure diagram of the lifting mechanism of the present invention; Figure 3 This is a closed structure diagram of the dust cover cloth of the present invention; Figure 4 This is a diagram of the contraction structure of the dust cover cloth of the present invention; Figure 5 This is a structural diagram of the discharge pipe connection of the present invention; Figure 6 The stirring blade of the present invention is provided with a structural diagram;
[0020] Figure 7 It is a structural diagram of the steel slag aggregate X-ray diffraction analysis test results of the present invention.
[0021] In the figure: 1 driving motor, 2 connecting rod, 3 moving block, 4 forward and reverse screw rods, 5 mounting plate, 6 first slider, 7 first slide groove, 8 support plate, 9 fixed plate, 10 stirring rod, 11 fixed rail, 12 hydraulic cylinder, 13 connecting plate, 14 protection box, 15 mixing box, 16 supporting column, 17 discharge pipe, 18 stirring blade, 19 protrusion, 20 dust cover cloth, 21 first vertical rod, 22 second slider, 23 second slide groove, 24 bottom plate, 25 bearing block, 26 second vertical rod. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0023] Reference Figure 1-6, which is mainly the mixing of the mixture in step S3 of the detection method of the test detection device for full-thickness long-life steel slag asphalt concrete pavement, including a bottom plate 24, the upper end of the bottom plate 24 supports a mixing box 15, and both sides of the mixing box 15 are provided with a lifting mechanism, the lifting mechanism includes a fixed block fixed on both sides of the mixing box 15, and a hydraulic cylinder 12 is fixed through the fixed block, and the ends of the piston rods of the two hydraulic cylinders 12 are fixed with a support plate 8, and the lower ends of the two fixed rails 11 are respectively fixed to one side of the upper ends of the two support plates 8. The two hydraulic cylinders 12 are connected by a synchronous control system, and the piston rods of the two hydraulic cylinders 12 are driven by the synchronous control system to rise or fall at the same time, thereby realizing the rise or fall of the upper structure; Two fixed rails 11 are fixed on the lifting mechanism, and two bearing blocks 25 are slidably connected to the two fixed rails 11. The guide rails 11 are provided with first slide grooves 7. First sliders 6 are fixed on both sides of the lower ends of the bearing blocks 25. One first slider 6 on one side of the lower ends of the two bearing blocks 25 is clamped in a first slide groove 7 on the same side to achieve stable sliding of the bearing blocks 25, thereby achieving stable adjustment; The upper ends of the two fixed rails 11 are provided with a reciprocating adjustment mechanism, which includes a connecting plate 13 fixed on both sides of the fixed rails 11, a mounting plate 5 is fixed on the upper end of one connecting plate 13, and a protection box 14 is installed on the upper end of the other connecting plate 13. A servo motor is installed in the protection box 14, and the end of the output shaft of the servo motor is connected to a forward and reverse screw 4, one end of the forward and reverse screw 4 is rotatably connected to one side of the mounting plate 5, and two moving blocks 3 are threadedly sleeved on the forward and reverse screw 4. The upper end of the moving block 3 is rotatably connected to two connecting rods 2, and the two on the same side are connected to the connecting rod 2. One end of each connecting rod 2 is connected to one end of a bearing block 25 for rotation. The servo motor drives the forward and reverse screws 4 to rotate through the rotation of the output shaft, and then drives the two moving blocks 3 to move toward the middle or to both sides at the same time, thereby realizing the expansion or contraction of the connecting rod 2, and then realizing the left and right movement of the stirring mechanisms on both sides, realizing the reciprocating stirring in the mixing box 15, improving the mixing quality of the mixed material, and at the same time, combined with the lifting and lowering of the hydraulic cylinder 12, further improving the mixing efficiency of the mixed material, ensuring the adequacy and effectiveness of the subsequent detection; The reciprocating adjustment mechanism is connected to the two bearing blocks 25. A stirring device is installed on one side of the bearing block 25. The stirring device includes a fixing plate 9 fixed to one side of the bearing block 25. A driving motor 1 is installed on the upper end of the fixing plate 9. A stirring rod 10 is connected to the end of the output shaft of the driving motor 1. A plurality of stirring blades 18 are connected to a circle of the stirring rod 10 at equal intervals. A plurality of protrusions 19 are provided at equal intervals on one side of the stirring blade 18. The driving motor 1 drives the stirring rod 10 and the stirring blade 18 to rotate by rotating the output shaft, thereby achieving stirring and mixing of the mixed material. The lower end of the stirring device extends into the mixing box 15, and a dust cover cloth 20 is slidably connected to one side of the upper end of the bottom plate 24, and the dust cover cloth 20 corresponds to the mixing box 15. Second slide grooves 23 are provided on both sides of the upper end of the bottom plate 24, and a second slider 22 is installed in the second slide groove 23. A first vertical rod 21 is fixed to the upper end of the second slider 22, and two second vertical rods 26 are fixed to one side of the upper end of the bottom plate 24. The upper ends of the two first vertical rods 21 and the two second vertical rods 26 are jointly fixed to the four corners of the lower end of the dust cover cloth 20. The dust cover cloth 20 can be driven to cover or open by sliding the first vertical rod 21, so as to realize dust prevention during mixing and avoid surrounding air pollution. At the same time, it is convenient to shrink and does not affect the addition of the mixed material. Support columns 16 are fixed at the four corners of the lower end of the mixing box 15, and the lower ends of the support columns 16 are fixed to the upper end of the bottom plate 24. A discharge pipe 17 is connected to the middle of the lower end of the mixing box 15. The discharge pipe 17 is a hose, and a valve is installed on the discharge pipe 17. After mixing is completed, the valve is opened to release the mixed mixture through the hose to the corresponding position, so as to carry out the next step of detection.
[0024] The present invention preferably uses steel slag produced by shallow pan water quenching method, with free calcium oxide content not higher than 3%, and water absorption rate not higher than 3%. After treatment, the steel slag aggregate is piled in the open air and aged for more than half a year; the steel slag aggregate mainly replaces aggregate larger than 4.75 mm, and basalt machine-made sand is used for fine aggregate below 4.75 mm. When steel slag asphalt concrete is used as the upper layer aggregate, its key performance indicators such as crushing value, abrasion and polishing value are excellent, and it has stronger crushing resistance compared with traditional basalt coarse aggregate. However, the presence of active calcium oxide in steel slag aggregate is the main reason for the expansion of steel slag aggregate when it encounters water; through pretreatment and technical adjustment, the volume stability of steel slag can be effectively controlled, and the long-term performance stability of steel slag in asphalt mixture can be achieved.
[0025] The present invention focuses on how to effectively control the volume stability of steel slag through pretreatment and technical adjustments to ensure its long-term performance stability in asphalt mixtures. In the pretreatment stage, various methods such as high-temperature calcination, chemical stabilization treatment and mechanical crushing are used to reduce the content of free calcium oxide in the steel slag and reduce the possibility of hydration reaction after it comes into contact with water. High-temperature calcination can promote the conversion of free calcium oxide into more stable compounds, thereby reducing its activity; chemical stabilization treatment is achieved by adding specific chemical reagents to react with free calcium oxide to generate stable compounds, further reducing the risk of volume expansion; mechanical crushing helps to refine the steel slag particles and improve its dispersion uniformity in the asphalt mixture, thereby improving the overall performance of the mixture.
[0026] In terms of technical adjustment, the present invention optimizes the mix ratio design of asphalt mixture, and improves the water damage resistance and durability of the mixture by adjusting the asphalt dosage, aggregate grading, and adding an appropriate amount of modifier. At the same time, we also carry out fine control of the construction processes such as mixing, paving, and compacting of the mixture to ensure that the steel slag asphalt concrete can be fully compacted during the construction process, reduce the void ratio, and further improve its impermeability and durability.
[0027] After a series of pretreatments and technical adjustments, steel slag asphalt concrete with stable performance and low cost was successfully prepared. This material not only has excellent wear resistance and anti-skid properties, but also can maintain good volume stability during long-term use, effectively reducing the cost of road maintenance. In addition, the application of steel slag asphalt concrete also promotes the resource utilization of steel industry waste, providing strong support for the construction of a green, low-carbon, circular development transportation system.
[0028] The steel slag asphalt concrete in the present invention is an innovative way to reduce costs and increase efficiency of full-thickness asphalt pavement, and its application prospects are broad. Through pretreatment and technical adjustments, the technical barrier of steel slag volume expansion has been successfully overcome, laying a solid foundation for the widespread application of steel slag in road materials.
[0029] Steel slag, a seemingly discarded industrial byproduct, actually contains huge utilization value. After fine processing, steel slag has high strength, excellent wear resistance and good anti-skid performance, which fully meets the requirements of asphalt concrete aggregate. Applying steel slag to the asphalt concrete wearing layer can not only effectively reduce the dependence on natural sand and gravel and reduce the cost of highway construction, but also turn waste into treasure, solve the environmental problems caused by steel slag stacking, and realize the conservation and efficient use of land resources. In addition, the use of steel slag can also promote the green transformation of the steel industry and promote the development of the entire industrial chain in a low-carbon and environmentally friendly direction.
[0030] Specifically, the application advantages of steel slag asphalt concrete are mainly reflected in the following aspects: (1) Significant environmental benefits: Using steel slag to replace part or all of the natural aggregates has greatly reduced the amount of sand and gravel mining, alleviated the damage to the natural mountains, and protected the ecological environment. At the same time, the reuse of steel slag reduces waste stacking, avoids the waste of land resources and potential environmental pollution.
[0031] (2) Reduced economic costs: As the price of natural aggregates continues to rise, steel slag, as an alternative material, has a relatively low cost and can effectively reduce the overall investment in highway construction. The economic benefits are particularly significant for large-scale, long-distance highway projects.
[0032] (3) Excellent performance: Steel slag asphalt concrete exhibits good mechanical properties and durability. Its high strength, wear resistance and anti-skid characteristics make the road surface more durable, extend the service life of the highway and reduce subsequent maintenance costs.
[0033] (4) Promoting industrial upgrading: The large-scale application of steel slag has promoted the development of related industrial chains, including the research and development of steel slag treatment technology and the innovation of asphalt concrete production technology, providing new growth points for related industries and helping to promote the green upgrade of the entire construction industry.
[0034] In order to realize the widespread application of steel slag in highway construction, some technical challenges need to be overcome, such as improving the efficiency of steel slag treatment, optimizing the mix design of steel slag asphalt concrete, and ensuring that its road performance meets the requirements of the specifications. At the same time, the government should introduce more encouraging policies, increase support for steel slag resource utilization projects, guide enterprises to increase R&D investment, and promote technological innovation and achievement transformation.
[0035] As an effective substitute for natural aggregates, steel slag has broad application prospects in asphalt concrete pavement projects. By strengthening policy guidance, technological innovation and market promotion, it can not only alleviate the pressure of natural resource shortage and reduce the cost of highway construction, but also promote resource recycling, realize green and low-carbon highway construction, and contribute to the construction of ecological civilization.
[0036] Analysis on the Material Characteristics of Steel Slag Asphalt Concrete 1. Comparison of steel slag aggregate performance Steel slag is gradually showing its unique value in asphalt concrete pavement construction. Especially when used as top layer aggregate, its key performance indicators such as crushing value, abrasion and polishing value are excellent. Compared with traditional basalt coarse aggregate, steel slag aggregate contains a large amount of iron oxide and is a product of melting and cooling, so it has a higher density and a denser texture. This feature not only gives steel slag excellent crushing resistance, but also significantly improves the bearing capacity and durability of the pavement.
[0037] Steel slag also performs well in terms of wear performance. Its hard material and rough surface structure make steel slag asphalt concrete have significant advantages in resisting wheel friction and natural environmental erosion. In addition, the polishing value of steel slag is relatively low, which means that the road surface can maintain good skid resistance, thereby improving driving safety.
[0038] However, there are still a number of challenges to overcome before steel slag can be widely used in asphalt concrete pavement construction. For example, the handling and processing of steel slag requires careful control to ensure that it meets the technical requirements of pavement engineering. At the same time, the storage and transportation of steel slag also need to consider environmental factors to avoid secondary pollution to the environment.
[0039] Steel slag aggregate performance benchmarking
[0040] 2. Chemical composition analysis Three common pavement aggregates, steel slag, basalt and limestone, were analyzed using an X-ray fluorescence analyzer. The data obtained revealed their unique chemical compositions, which are crucial to understanding their performance in asphalt concrete.
[0041] The composition analysis results of steel slag show that its main component is calcium oxide. Although its content is slightly lower than that of limestone aggregate, it still constitutes the cornerstone of steel slag. Following closely is iron oxide, with a content of up to 24.55%. This is a significant feature that distinguishes steel slag from other natural aggregates, and is also an important reason for its outstanding hardness and wear resistance. The content of silicon dioxide in steel slag is 19.24%, which also occupies an important position. In addition, steel slag also contains a small amount of magnesium oxide and aluminum oxide, and their content is less than 10%, but these trace components also have a subtle effect on the overall performance of steel slag.
[0042] Limestone aggregate is known for its high content of calcium oxide and silicon dioxide, which together account for about 61%. This composition gives limestone excellent mechanical properties and stability, making it an indispensable component of traditional asphalt concrete.
[0043] The composition of basalt aggregates presents a different picture. Its main component is silicon dioxide, which is as high as 58%, which makes basalt have high hardness and wear resistance. Aluminum oxide is also an important component of basalt, while the content of calcium oxide is relatively low. This composition distribution gives basalt unique physical and chemical properties.
[0044] By comparing the composition of these three aggregates, we can gain a deeper understanding of their differences in behavior in asphalt concrete. Steel slag exhibits excellent resistance to crushing, wear and skid due to its high content of iron oxide and dense internal structure; limestone aggregate provides good mechanical support with its high calcium and silicon content; and basalt aggregate ensures the hardness and durability of the pavement with its high silicon content. These composition analysis data provide a scientific basis for the selection of pavement materials, mix design and performance prediction, which will help promote the green and high-performance development of asphalt concrete pavements.
[0045]
[0046] 3. X-ray diffraction analysis By using X-ray diffraction analysis technology to conduct in-depth crystal phase analysis of steel slag aggregates, valuable information about the internal crystal structure of steel slag aggregates was obtained. The following is a detailed interpretation of the XRD analysis results and a further discussion on the phenomenon of steel slag aggregate swelling when exposed to water.
[0047] The XRD spectrum of steel slag aggregate clearly reveals its main crystalline phase composition. These crystalline phases mainly include the following parts: Calcium oxide: As an important component of steel slag, calcium oxide usually exists in a free state and has high activity. When exposed to water, free calcium oxide will undergo hydration reaction to generate calcium hydroxide, accompanied by significant volume growth, which is the main reason for the expansion of steel slag aggregates when exposed to water.
[0048] Calcium aluminum metal oxide solid solution: This solid solution is a complex compound formed during the cooling process of steel slag. Its chemical composition and crystal structure are relatively stable, and it has an important influence on the mechanical properties and durability of steel slag.
[0049] Tricalcium silicate and dicalcium silicate: These two compounds are the main components of cement clinker and are also present in steel slag in higher proportions. They play a key role in the hardening process and strength development of steel slag.
[0050] Calcium iron metal oxide solid solution: Although the XRD spectrum does not directly show the specific crystal phase of iron oxide, based on the analysis results and process background, we can infer that the iron oxide mainly comes from the quicklime added during the smelting process. The presence of iron oxide not only affects the color and magnetic properties of the slag, but may also affect the overall performance of the slag through interaction with other components.
[0051] Reference Figure 7 As mentioned above, the free calcium oxide in steel slag aggregate is the main reason for its expansion when it comes into contact with water. This expansion phenomenon not only affects the stability of steel slag aggregate in asphalt mixture, but may also cause damage to the pavement structure. Therefore, how to effectively control the expansion of steel slag aggregate has become a key issue that needs to be solved in its practical application.
[0052] 4. Electron Probe Using advanced electron probe technology, the surface of steel slag aggregates was meticulously analyzed, revealing the mystery of its internal component distribution. The analysis results show that calcium oxide in steel slag aggregates exists in a significant block form and is extremely unevenly distributed. This unique component distribution pattern directly leads to a large discreteness of the free calcium oxide content in steel slag in actual testing, emphasizing the importance of sampling location and method for the accuracy of test results.
[0053] Further investigation of the performance characteristics of steel slag revealed that its poor volume stability is a particular concern. This is mainly due to the large amount of free calcium oxide and a small amount of free magnesium oxide contained in the steel slag. When these free oxides encounter moisture, a chemical reaction occurs, resulting in a significant volume expansion, which can even reach twice the original volume. This volume expansion phenomenon poses a serious threat to the stability and durability of the road surface.
[0054] Therefore, among the many indicators for controlling the volume expansion of steel slag, the content of free calcium oxide is undoubtedly the most critical one. In order to gain a deeper understanding of the actual situation of free calcium oxide in steel slag, we selected steel slag samples produced by two different manufacturers, Laiwu and Rizhao, for testing. These samples have different forms, both powdery and granular, ensuring the comprehensiveness and representativeness of the test.
[0055] The test results show that the free calcium oxide content in different samples is indeed quite discrete, with the highest value reaching 2.9% and the lowest value being only 0.08%. Despite this, the average content of all samples is still controlled at 1.58%, meeting the requirement of less than 3% in the specification. This discovery not only provides us with valuable data on the free calcium oxide content of steel slag, but also provides an important reference for the subsequent treatment and application of steel slag.
[0056] Through the analysis of EPMA results, we have a deeper understanding of the composition distribution and performance characteristics of steel slag aggregates. At the same time, the detection of free calcium oxide content also provides strong technical support for controlling the volume expansion of steel slag and optimizing its application performance. In the future, we will continue to deepen the research on road materials such as steel slag to contribute to the green and sustainable development of highway construction.
[0057] Study on the influence of steel slag aggregate on the performance of asphalt concrete 1. Influence of Surface Characteristics of Steel Slag Aggregate on the Performance of Asphalt Concrete (1) Research on characteristics and characterization methods of steel slag aggregate After an in-depth analysis of the basic physical and chemical properties of steel slag, a quantitative characterization method for the particle shape and surface characteristics of steel slag aggregates was successfully explored. By introducing key indicators such as shape factor, surface roughness, and porosity, the geometric morphology and surface characteristics of steel slag aggregates can be more accurately described. At the same time, a comparative study of steel slag and natural aggregates revealed significant differences in density, hardness, wear resistance, etc., but steel slag, due to its unique composition and structure, is even superior to natural aggregates in some properties.
[0058] In addition, the aging law model of steel slag was also studied. Through long-term monitoring of the physical and chemical properties of steel slag under natural stacking conditions, we found that the content of free calcium oxide and free magnesium oxide gradually decreased with the extension of aging time, and the volume stability also increased. This discovery provides an important basis for the stabilization treatment of steel slag and helps to solve the volume expansion problem that steel slag may encounter in application.
[0059] (2) Study on the influence of steel slag aggregate characteristics on asphalt concrete composition design In the composition design of asphalt concrete, the internal pore structure and asphalt dosage are key indicators, and the particle shape and surface characteristics of steel slag aggregate have a significant impact on these indicators. Steel slag aggregate usually has irregular particle shape and rough surface, which may bring advantages or challenges in asphalt concrete.
[0060] The irregular particle shape of steel slag aggregate helps to increase the skeleton stability of asphalt concrete and improve the bearing capacity of the pavement. At the same time, its rough surface enhances the adhesion with asphalt, helps to reduce spalling and wear, and improves the durability of the pavement. However, these characteristics may also lead to an increase in the porosity inside the asphalt concrete, affecting the drainage performance and anti-skid performance of the pavement.
[0061] In order to optimize the composition design of asphalt concrete, it is necessary to comprehensively consider the characteristics of steel slag aggregate and the performance requirements of asphalt concrete. In terms of gradation composition, the relationship between porosity and skeleton stability can be balanced by adjusting the dosage and particle size distribution of steel slag aggregate. In terms of asphalt dosage, it is necessary to make appropriate adjustments based on the adsorption capacity of steel slag aggregate to ensure the cohesion and construction workability of asphalt concrete.
[0062] In addition, the characteristics of steel slag aggregates have different effects on the composition design of asphalt concrete of different structural types. For suspended dense asphalt concrete, the high adsorption capacity of steel slag aggregates helps to form a stable skeleton structure; while for skeleton void asphalt concrete, more attention should be paid to the effect of steel slag aggregates on porosity to avoid affecting the drainage performance of the pavement.
[0063] (3) Study on the influence of steel slag aggregate-asphalt interface performance In the process of deepening the application research of steel slag aggregate in asphalt concrete, the steel slag-asphalt interface delamination and peeling test method was innovatively adopted to comprehensively characterize the selective absorption and adsorption behavior of steel slag on asphalt. This method not only reveals how steel slag aggregate affects the proportion of the four components of asphalt, but also deeply explores its influence mechanism on the rheological properties and chemical composition of asphalt. Through sophisticated experimental design and data analysis, it is found that the selective adsorption behavior of steel slag has a significant effect on key indicators such as the viscosity and elastic recovery capacity of asphalt, which provides an important theoretical basis for further optimizing the performance of asphalt concrete.
[0064] At the same time, in order to comprehensively evaluate the adhesion performance of steel slag aggregates and asphalt, we implemented a mechanical pull-out test. This test effectively evaluates the interfacial bonding strength between steel slag aggregates and asphalt by simulating the mechanical environment under actual use conditions. The test results show that steel slag aggregates have good adhesion performance with asphalt due to their unique surface properties and chemical composition, which lays a solid foundation for the widespread application of steel slag in asphalt concrete.
[0065] On this basis, a slag-asphalt interface mechanical characteristics model was further constructed. This model comprehensively considers multiple factors such as the particle shape, surface roughness, chemical composition of slag aggregates and their selective adsorption behavior on asphalt, and can accurately predict the mechanical properties of the slag-asphalt interface. Through this model, the specific influence of the selective adsorption of slag on the mechanical properties of the interface was deeply analyzed, providing scientific guidance for optimizing the use of slag aggregates in asphalt concrete.
[0066] In addition, the selective adsorption behavior of steel slag has a potential impact on the long-term performance of asphalt concrete. Therefore, in practical applications, it is necessary to regulate the selective adsorption behavior of steel slag through reasonable grading design, asphalt modification and other means to give full play to its advantages and avoid potential adverse effects.
[0067] Through the steel slag-asphalt interface delamination test, mechanical pull-out test and the construction of the interface mechanical characteristic model, the interaction mechanism between steel slag aggregate and asphalt and its influence on the performance of asphalt concrete were deeply studied. These research results not only provide theoretical basis and technical support for the efficient use of steel slag in asphalt concrete, but also contribute to the sustainable development of road construction.
[0068] (4) Study on the influence of steel slag aggregate characteristics on asphalt concrete performance The AIMS system is used to analyze the special particle shape and surface characteristics of steel slag, and the influence of steel slag aggregate on the performance of asphalt concrete of different grading types is deeply analyzed. The influence of the particle shape and surface characteristics of steel slag aggregate on the road performance of asphalt concrete such as resistance to water damage, resistance to high temperature rutting, resistance to low temperature cracking, and resistance to fatigue is explored.
[0069] 2. Study on the physicochemical characteristics of aged steel slag and the performance of asphalt concrete (1) Research on the aging reaction mechanism and physical and chemical properties of steel slag In the study of the resource utilization of steel slag, it is particularly important to deeply analyze the changes in the mineral phase of steel slag and its aging reaction mechanism. Through systematic mineralogical analysis, the types of phases involved in the aging reaction were clarified, including key components such as dicalcium silicate, tricalcium silicate, free calcium oxide and free magnesium oxide. These components undergo complex chemical reactions during the aging process and gradually transform into more stable mineral phases, such as hydrated calcium silicate gel, which significantly changes the physical and chemical properties of steel slag.
[0070] The aging reaction has a particularly significant effect on the microscopic morphology of the steel slag surface. Scanning electron microscopy observations show that with the extension of aging time, the steel slag surface gradually becomes smoother, and the porosity and number of cracks are significantly reduced, which is due to the recrystallization and rearrangement of minerals during the aging process. At the same time, element distribution analysis shows that the elements in the aged steel slag are more evenly distributed, which helps to reduce internal stress concentration and improve the overall stability of the material.
[0071] In terms of thermal stability, the results of differential thermal analysis and thermogravimetric analysis show that the aged steel slag has a higher thermal decomposition temperature and a lower heat loss rate, indicating that its thermal stability has been significantly improved. This is of great significance for the application of steel slag in high temperature environments, such as as a refractory material or aggregate in road construction.
[0072] In addition, the aging reaction also improves the temperature rise characteristics of steel slag. In applications such as cement concrete, the temperature rise characteristics of steel slag are directly related to the early strength and durability of the material. The study found that the heat released by the aged steel slag during the hydration process is more gradual, which helps to reduce the temperature stress inside the concrete and prevent cracking, thereby improving the long-term performance of the concrete.
[0073] (2) Preparation of steel slag aggregate and study on its controllability After in-depth research on the physical and chemical characteristics of aged steel slag, the mechanism of deterioration of steel slag aggregate performance was further explored. During the aging process, the performance of steel slag aggregate may gradually deteriorate due to the transformation of mineral phases and changes in microstructure. This is mainly manifested in the solidification of dust on the aggregate surface and the variation of aggregate specifications.
[0074] The solidification of dust on the aggregate surface is mainly due to the hydration reaction of the mineral phase during the aging process. These reactions lead to the formation of a relatively hard solidified layer on the aggregate surface, which reduces the adhesion between the aggregate and asphalt. The variation of aggregate specifications may be due to the accumulation of small changes in volume during the aging process. Although this change is small, it may have a significant impact on pavement performance in large-scale applications.
[0075] In order to improve the production process and prepare steel slag aggregate with controllable performance, technical innovation was carried out based on the aggregate performance deterioration mechanism. By optimizing the aging conditions, such as adjusting the aging time, temperature and humidity, the solidification of the aggregate surface dust and the size variation were successfully controlled. At the same time, advanced crushing and screening technologies were introduced to ensure the size stability of the aggregate.
[0076] In the prepared steel slag aggregate, key indicators such as aggregate surface cleanliness, volume stability and specification stability were analyzed. The results show that by improving the production process, the surface cleanliness of the aggregate is significantly improved, reducing dust pollution; the volume stability is also effectively controlled, avoiding performance degradation due to volume changes; at the same time, the stability of the aggregate specification is also guaranteed, providing high-quality raw materials for engineering applications such as asphalt concrete.
[0077] (3) Study on the performance of aged steel slag asphalt concrete In exploring the application potential of aged steel slag in asphalt concrete, the Superpave method was used to design aged steel slag asphalt concrete, and its performance was comprehensively and in-depth evaluated.
[0078] First, in terms of volume stability, through long-term immersion tests and freeze-thaw cycle tests, it was found that aged steel slag asphalt concrete exhibited good volume stability, and its volume change rate was much lower than that of traditional asphalt concrete, which was due to the effective digestion of free calcium oxide in the aged steel slag.
[0079] Secondly, in terms of fatigue resistance, we evaluated the fatigue life of aged steel slag asphalt concrete through a four-point bending fatigue test. The results showed that the fatigue life of aged steel slag asphalt concrete was significantly better than that of traditional asphalt concrete at the same stress level, which was mainly attributed to the high strength and good skeleton support of steel slag aggregate.
[0080] In terms of water damage resistance, Marshall immersion test and freeze-thaw splitting test were carried out. The results showed that the aged steel slag asphalt concrete has a high water stability index and can effectively resist water damage, which is due to the good adhesion between steel slag aggregate and asphalt and the optimization of aggregate surface microstructure.
[0081] In addition, in terms of low-temperature crack resistance, through low-temperature bending tests, it was found that aged steel slag asphalt concrete can still maintain good flexibility under low-temperature conditions, and its crack resistance is better than that of traditional asphalt concrete. In terms of high-temperature deformation resistance, through rutting tests, we verified that aged steel slag asphalt concrete can still maintain good stability and deformation resistance at high temperatures.
[0082] In terms of thermal properties, the thermal conductivity and thermal expansion of aged steel slag asphalt concrete were studied. The results showed that its thermal conductivity was moderate and its thermal expansion coefficient was low, which helped to reduce pavement deformation and cracking caused by temperature changes.
[0083] (4) Research on the mechanism of water damage and performance improvement technology of aged steel slag asphalt concrete The asphalt film peeling test and tensile failure test methods were used, combined with modern characterization techniques such as scanning electron microscopy, to clarify the damage mechanism of hot water damage and freeze-thaw damage on the aged steel slag asphalt system; the improvement effect of organic sealants and inorganic anti-stripping agents on the water damage resistance of aged steel slag asphalt concrete was studied.
[0084] Study on design principle and anti-expansion technology of steel slag asphalt concrete 1. SMA-13 asphalt mixture raw material inspection and appearance, physical and mechanical properties analysis The raw materials such as limestone, basalt, asphalt in SMA-13 asphalt mixture were tested, the slag-forming process and morphological characteristics of steel slag were investigated, the physical and mechanical properties, free calcium oxide content, volume stability of steel slag were tested, and the performance was compared with that of commonly used stones in existing highways; X-ray CT scanning technology was used to analyze the microstructure of steel slag coarse aggregate.
[0085] 2. Design and optimization of steel slag SMA-13 asphalt mixture ratio By analyzing and studying the material properties of steel slag, the design process and key points of steel slag asphalt mixture ratio were optimized, and the effective relative density of steel slag was measured using SBS modified asphalt. The volumetric mixing ratio method was adopted to make the volumes of aged steel slag of different diameters replace the basalt gravel of the same particle size to prepare SMA-13 asphalt mixtures with different steel slag dosages. At the same time, a control group of basalt SMA-13 asphalt mixture was prepared for comparative analysis.
[0086] 3. Performance analysis and evaluation of SMA-13 asphalt mixture with different steel slag content Hamburger wheel rutting and dynamic modulus tests were conducted on SMA-13 asphalt mixtures with different steel slag contents to analyze their high and low temperature performance, water damage resistance, shear resistance, and volume stability; X-ray CT scanning technology was used to compare and analyze their structures. Through various performance tests, the optimal volumetric content of steel slag in SMA-13 asphalt mixtures was found.
[0087] 4. Research on anti-expansion technology of steel slag SMA-13 asphalt mixture Before steel slag is used in road engineering, in order to ensure that its volume stability meets the requirements, the solidified steel slag needs to be further processed. According to different control principles, it can be divided into three types: promoting calcium oxide hydration, inhibiting calcium oxide hydration and eliminating calcium oxide. Promoting calcium oxide hydration means inducing calcium oxide to undergo hydration reaction before steel slag is used as recycled aggregate, releasing expansion potential in advance, thereby reducing the volume expansion of steel slag after it is used in road engineering. The main methods include natural aging, hydrothermal aging, steam aging, etc. Inhibiting calcium oxide hydration means spraying or soaking steel slag with surface coating materials or modifiers to form a protective layer on the surface of steel slag that can isolate active substances from water, making the hydration reaction impossible. Eliminating calcium oxide means adding a certain amount of admixture to react with calcium oxide before or during the use of steel slag, thereby reducing the risk of expansion.
[0088] Natural aging is to store steel slag outdoors so that the active ingredients in it can fully contact and react with the atmosphere and water in the natural environment, and then digest the steel slag before it is recycled. Natural aging is currently the most important treatment method for bulk steel slag solid waste. Generally, steel slag needs to be naturally aged for 6-12 months before it can be used as aggregate for road projects. Compared with natural aging, hydrothermal aging can accelerate the calcium oxide hydration reaction rate and improve aging efficiency.
[0089] With the increase of hydrothermal aging temperature and aging time, the volume expansion rate of steel slag shows an overall downward trend. At room temperature, the volume expansion rate of steel slag after immersion in water for 28 days is 1.3%, which is equivalent to immersion in water at 60°C for 7 days, indicating that increasing the temperature can significantly improve the inhibition effect of steel slag volume expansion. In addition, at the same temperature, increasing the immersion time can also increase the expansion inhibition rate. However, when the immersion temperature is 90°C, the expansion rate of steel slag has hardly changed after the immersion time increases from 15d to 28d. Based on the above analysis, it can be seen that temperature can significantly reduce the potential expansion of steel slag. Therefore, under the existing test conditions, the immersion temperature should be increased as much as possible to improve the expansion inhibition effect, but attention should be paid to controlling the optimal immersion time to avoid waste of time and resources.
[0090] Through comparative analysis of the performance of steel slag aggregate before and after aging, and the preparation of steel slag SMA-13 asphalt mixture by the method of mixing unaged steel slag with limestone gravel, its volume expansion rate was tested, and an estimation model for its volume expansion was established. The steel slag dosage at the critical value of the volume expansion rate required by the specification was calculated. Based on the considerations of meeting the requirements of the specification and maximizing the economic benefits, the optimal dosage of unaged steel slag was determined, and the road performance of the anti-expansion steel slag SMA-13 asphalt mixture was analyzed.
[0091] The application of steel slag aggregate in asphalt concrete wearing layer has gradually attracted attention. To ensure the quality of steel slag aggregate, steel slag produced by shallow pan water quenching method is preferred. This process can effectively control the free calcium oxide content of steel slag to no more than 3% and the water absorption rate to no more than 3%. After crushing, dust removal, iron removal, screening and other processes, the steel slag aggregate is piled in the open air and aged for more than half a year, which can significantly reduce its water expansion rate and ensure that the water expansion rate is no more than 1.8%, thereby improving the volume stability of steel slag aggregate.
[0092] Asphalt concrete is a multiphase composite material, its volume stability is not solely determined by the expansion properties of aggregates. In steel slag asphalt mixture, the wrapping of steel slag by asphalt film can prevent the contact between steel slag aggregate and water, which reduces the expansion risk of steel slag to a certain extent. However, the expansion of steel slag has a certain randomness, so the volume stability of steel slag asphalt mixture should be tested before application. By comparing the coarse and fine aggregates are both cold-abandoned steel slag for 3 months and the coarse aggregate is cold-abandoned steel slag for 3 months and the fine aggregate is limestone, the water expansion rate test results are shown in the table:
[0093] The water expansion rate of crude steel fine aggregate asphalt concrete is reduced by 0.37% compared with that of pure steel slag asphalt concrete, indicating that the steel slag replacement scheme of crude steel fine aggregate can effectively reduce the expansion risk of steel slag asphalt concrete.
[0094] In summary, after the process or aging treatment, the content of calcium oxide in steel slag is effectively reduced. Even if the steel slag asphalt mixture is soaked in water for a long time, the volume expansion caused by the reaction of the small amount of calcium oxide remaining with water is easily offset by the voids in the asphalt mixture, and the volume expansion is not obvious. In practical applications, the replacement ratio of steel slag should be strictly controlled according to the conditions of the raw materials to ensure that the expansion characteristics meet the requirements.
[0095] In the asphalt concrete wearing layer, steel slag aggregate mainly replaces aggregate larger than 4.75mm. For fine aggregates below 4.75mm, it is recommended to use basalt or diabase machine-made sand. For low-grade roads, limestone machine-made sand can also be used. This aggregate matching ratio can give full play to the advantages of steel slag aggregate in wear resistance and skid resistance, while ensuring the overall performance of asphalt mixture.
[0096] It is worth noting that the apparent relative density of steel slag aggregate is as high as 3.3-3.5g / cm3, which is much greater than that of natural aggregate. Therefore, in the mix design, we use volume fraction to measure steel slag aggregate and convert it into mass fraction in actual production. In addition, in order to further improve the crack resistance of the asphalt concrete wearing layer and prevent segregation, we recommend adding 3-5‰ polyester fiber, lignin fiber or mineral fiber.
[0097] Due to the large specific heat capacity and high water absorption rate of steel slag aggregate, in the production process of steel slag asphalt wearing course mixture, it is necessary to appropriately increase the heating temperature according to the amount of steel slag added to ensure the uniformity and stability of the mixture. Through this series of measures, the overall performance of the asphalt concrete wearing course can be effectively improved, providing a more high-quality and durable material choice for road construction.
[0098] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A testing device for a full-thickness long-life steel slag asphalt concrete pavement, comprising a base plate (24), characterized in that: The upper end of the bottom plate (24) supports a mixing box (15), and lifting mechanisms are provided on both sides of the mixing box (15). Two fixed rails (11) are fixed on the lifting mechanisms, and two bearing blocks (25) are slidably connected to the two fixed rails (11). A reciprocating adjustment mechanism is provided at the upper ends of the two fixed rails (11), and the reciprocating adjustment mechanism is connected to the two bearing blocks (25). A stirring device is installed on one side of the bearing blocks (25), and the lower end of the stirring device extends into the mixing box (15). A dust cover cloth (20) is slidably connected to one side of the upper end of the bottom plate (24), and the dust cover cloth (20) corresponds to the mixing box (15).
2. The testing and detecting device for full-thickness long-life steel slag asphalt concrete pavement according to claim 1 is characterized in that: The lifting mechanism comprises fixed blocks fixed on both sides of the mixing box (15), a hydraulic cylinder (12) passing through the fixed block, the ends of the piston rods of the two hydraulic cylinders (12) are fixed with support plates (8), the lower ends of the two fixed rails (11) are respectively fixed to one side of the upper ends of the two support plates (8), and the two hydraulic cylinders (12) are connected using a synchronous control system.
3. The testing and detecting device for full-thickness long-life steel slag asphalt concrete pavement according to claim 1 is characterized in that: The reciprocating adjustment mechanism comprises connecting plates (13) fixed on both sides of the fixed rail (11), wherein a mounting plate (5) is fixed to the upper end of one of the connecting plates (13), and a protection box (14) is installed to the upper end of the other connecting plate (13), wherein a servo motor is installed in the protection box (14), and the end of the output shaft of the servo motor is connected to a forward and reverse screw rod (4), one end of the forward and reverse screw rod (4) is rotatably connected to one side of the mounting plate (5), and two moving blocks (3) are threadedly sleeved on the forward and reverse screw rod (4), and the upper end of the moving block (3) is rotatably connected to two connecting rods (2), and one end of the two connecting rods (2) on the same side is rotatably connected to one end of a bearing block (25) together.
4. The testing and detecting device for full-thickness long-life steel slag asphalt concrete pavement according to claim 1 is characterized in that: The stirring device comprises a fixing plate (9) fixed to one side of a bearing block (25), a driving motor (1) being mounted on the upper end of the fixing plate (9), a stirring rod (10) being connected to the end of an output shaft of the driving motor (1), a plurality of stirring blades (18) being connected to one side of the stirring rod (10) at equal intervals, and a plurality of protrusions (19) being arranged at equal intervals on one side of the stirring blade (18).
5. The testing and detecting device for full-thickness long-life steel slag asphalt concrete pavement according to claim 1 is characterized in that: Second slide grooves (23) are provided on both sides of the upper end of the bottom plate (24), a second slide block (22) is installed in the second slide groove (23), a first vertical rod (21) is fixed to the upper end of the second slide block (22), two second vertical rods (26) are fixed to one side of the upper end of the bottom plate (24), and the upper ends of the two first vertical rods (21) and the two second vertical rods (26) are fixed together at the four corners of the lower end of the dust cover cloth (20).
6. The testing and detecting device for full-thickness long-life steel slag asphalt concrete pavement according to claim 1 is characterized in that: The guide rail (11) is provided with a first slide groove (7), and first sliders (6) are fixed on both sides of the lower end of the bearing block (25), and a first slider (6) on one side of the lower end of the two bearing blocks (25) is clamped in a first slide groove (7) on the same side.
7. The testing and detecting device for full-thickness long-life steel slag asphalt concrete pavement according to claim 1 is characterized in that: Support columns (16) are fixed at the four corners of the lower end of the mixing box (15), and the lower ends of the support columns (16) are fixed to the upper end of the bottom plate (24). A discharge pipe (17) is connected to the middle of the lower end of the mixing box (15), and the discharge pipe (17) is a hose. A valve is installed on the discharge pipe (17).
8. The method for testing and detecting the full-thickness long-life steel slag asphalt concrete pavement according to claim 1 is characterized in that: The following steps are involved: S1, pretreatment stage, high temperature calcination, chemical stabilization and mechanical crushing are used to treat the steel slag; S2, technical adjustment stage, optimize the mix design of asphalt mixture, adjust the asphalt dosage, aggregate gradation and add appropriate amount of modifier to improve the water damage resistance and durability of the mixture; S3. Finely control the mixing, spreading and pressing processes of the mixture to improve its impermeability and durability; S4, after pretreatment and technical adjustment, steel slag asphalt concrete is prepared; S5. Use X-ray fluorescence analyzer to analyze the composition of three common road aggregates: steel slag, basalt and limestone; S6. By using X-ray diffraction analysis technology to conduct in-depth crystal phase analysis on steel slag aggregates, information about the internal crystal structure of steel slag aggregates was obtained; S7, using electron probe technology to conduct detailed surface analysis of steel slag aggregate to reveal its internal component distribution; S8. Through the analysis of the basic physical and chemical properties of steps S1-S7, a quantitative characterization method for the particle shape and surface characteristics of steel slag aggregate is explored, and key indicators such as shape factor, surface roughness, and porosity are introduced to accurately describe the geometric morphology and surface characteristics of steel slag aggregate; S9. The slag-asphalt interface delamination test method is used to fully characterize the selective absorption and adsorption behavior of slag on asphalt; S10. Conduct mechanical pull-out tests to evaluate the adhesion performance between steel slag aggregate and asphalt; S11. Construct the mechanical characteristic model of slag-asphalt interface; S12, through the slag-asphalt interface delamination test, mechanical pull-out test and interface mechanical characteristic model construction of steps S9-S11, the interaction mechanism between slag aggregate and asphalt and its influence on the performance of asphalt concrete are studied; S13. Use AIMS system to analyze the special particle shape and surface characteristics of steel slag, deeply analyze the influence of steel slag aggregate on the performance of asphalt concrete of different grading types, and explore the influence of the particle shape and surface characteristics of steel slag aggregate on the road performance of asphalt concrete such as water damage resistance, high temperature rutting resistance, low temperature cracking resistance, fatigue resistance, etc. S14. Explore the application potential of aged steel slag in asphalt concrete, design aged steel slag asphalt concrete using the Superpave method, and conduct a comprehensive evaluation of its performance.
9. The method for testing and detecting the full-thickness long-life steel slag asphalt concrete pavement according to claim 8 is characterized in that: According to step S1, high temperature calcination can convert free calcium oxide into a more stable compound, thereby reducing its activity; Chemical stabilization treatment adds specific chemical reagents to react with free calcium oxide to form stable compounds, further reducing the risk of volume expansion; Mechanical crushing helps to refine steel slag particles and improve their dispersion uniformity in asphalt mixture, thereby improving the overall performance of the mixture.
10. The method for testing and detecting the full-thickness long-life steel slag asphalt concrete pavement according to claim 8 is characterized in that: According to step S14, the asphalt film peeling test and the tensile failure test method are used, combined with the use of modern scanning electron microscope characterization technology, to clarify the damage mechanism of hot water damage and freeze-thaw damage to the aged steel slag asphalt system; The improvement effect of organic sealants and inorganic anti-stripping agents on the water damage resistance of aged steel slag asphalt concrete was studied.